METAFORA BERANJAK DEWASA DALAM LIRIK LAGU “TAKUT” KARYA IDGITAF: KAJIAN LINGUISTIK KOGNITIF - Anan Taturia, Dwika Muzakky; Wibiasty, Patricia Elsa Marchelia (Epigram, 2024)
This study aims to analyze the metaphor of "beranjak dewasa" in the song lyrics of “Takut” by IDGITAF. Utilizing the Conceptual Metaphor Theory by Lakoff and Johnson (1980), the structural metaphors in the song's lyrics were examined through the mapping of source and target domains, as well as their image schemas. This research employs a descriptive qualitative approach. Data analysis was conducted using the distributional method and advanced techniques for immediate constituent analysis, while data collection was carried out through the observation method with note-taking techniques. The analysis revealed five structural metaphors: (1) ambisiku bergejolak, (2) antusias tak karuan, (3) mimpi yang kukejar, (4) mimpi yang terkubur, dan (5) mengorbankan waktu tidur. The image schema depicted from these metaphors is existence. The metaphor of "beranjak dewasa" represents a process filled with enthusiasm, struggle, and sacrifice. This metaphor provides a depiction for today's youth who are transitioning into their 20s, a phase where they encounter a different world where expectations do not always align with dreams or aspirations. The findings of this study affirm the song's message that every young person will inevitably go through their youth and must prepare to enter adulthood.